3D Printed Platform for Impedimetric Sensing of Liquids and Microfluidic Channels - Sebechlebská, Táňa; Vaněčková, Eva; Choińska-Młynarczyk, Marta Katarzyna; Navrátil, Tomáš; Poltorak, Lukasz; Bonini, Andrea; Vivaldi, Federico; Kolivoška, Viliam (Analytical chemistry (Washington), 2022)
Fused deposition modeling 3D printing (FDM-3DP) employing electrically conductive filaments has recently been recognized as an exceptionally attractive tool for the manufacture of sensing devices. However, capabilities of 3DP electrodes to measure electric properties of materials have not yet been explored. To bridge this gap, we employ bimaterial FDM-3DP combining electrically conductive and insulating filaments to build an integrated platform for sensing conductivity and permittivity of liquids by impedance measurements. The functionality of the device is demonstrated by measuring conductivity of aqueous potassium chloride solution and bottled water samples and permittivity of water, ethanol, and their mixtures. We further implement an original idea of applying impedance measurements to investigate dimensions of 3DP channels as base structures of microfluidic devices, complemented by their optical microscopic analysis. We demonstrate that FDM-3DP allows the manufacture of microchannels of width down to 80 μm.